Prediction of from at the LHC for the IMDS3 model. (24th September 2015) - Fortes, E C F S; Machado, A C B; Montaño, J; Pleitez, V
Abstract: We consider the decays in the context of an extension of the Standard Model with two inert doublets and an additional S 3 symmetry. This model contributes to for these processes through new charged scalar-loops. Comparing our with more precise available experimental data we can predict the behavior of since they depend on the same parameters. Our estimation for this channel is 1.05 times the standard model value, but it can be as high as 1.16 if we consider the uncertainty from the data, and as low as 0.96 if we consider